Factors contributing to primary care givers' delay in presenting children with chronic kidney disease for medical care in Ghana - Amoah, Abigail (Division of Nursing and Midwifery, 2017)
Chronic kidney disease (CKD) in children has become a public health problem in Ghana. The researcher observed that the primary care givers of these children present them late for medical care. This ignited the researcher to conduct this study to identify factors that contribute to primary care givers' delay in seeking early medical care for children with CKD. The purpose of the study was to explore and describe the factors that contribute to primary care givers' delay in presenting children who suffer from CKD for medical care in Ghana. A descriptive qualitative design was used to answer the research question: What factors contribute to primary care givers' delay in presenting children with CKD for medical care in Ghana? Convenience sampling was used to recruit ten primary care givers of children admitted for CKD at the Paediatric Renal Unit of Komfo Anokye Teaching Hospital in Kumasi, Ghana, to participate in the study. Semi-structured interviews and field notes were used to collect data. The thematic data analysis approach of Colaizzi (1978) was used, and the ecological model of Schneider (2017) assisted in organising themes and subthemes. The themes which emerged are: intrapersonal-related factors contributing to delay; interpersonal-related factors contributing to delay; community-related factors contributing to delay; and political-related factors contributing to delay. These were directly related to the research question. A fifth theme which emerged serendipitously is the perceived need for community awareness about CKD. The findings revealed that intrapersonal, interpersonal, community and political level factors influence primary care givers' decisions in seeking medical care for their children. At intrapersonal level factors that played a role were personal attitudes and beliefs; primary care givers' beliefs in traditional medicine as a cure for CKD; their lack of knowledge on CKD and its management; primary care givers' financial constraints; and their beliefs in ancestral spiritual powers for healing. At interpersonal level factors included primary care givers' lack of family support and marital conflicts. At community level factors included primary care givers' delayed referral from the local health facility; incorrect advice received from family and neighbours on management; mismanagement of the disease at the local health facility; and misdiagnosis by neighbours. At political level the distance of the primary care givers' homes from the hospital can contribute to delays. One of the recommendations of the study is development and implementation of a national referral policy for CKD patients to guide health practitioners at the districts. Early referral for appropriate treatment of children with CKD can slow progression of the disease and prevent early mortality. Awareness campaigns need to be developed and implemented by the Ghana Kidney Association to provide health educational programmes for health professionals and communities. Further research using a larger sample or quantitative research methods is also recommended, to gain a better understanding of the factors contributing to delays in presentation of children with CKD in Ghana.